Kolegialitas: Suatu Bentuk Formasi Berkelanjutan Imam - Edison R.L. Tinambunan (Sekolah Tinggi Widya Sasana, 2020)
Ongoing formation is a subject which is very actual at this present time in relation with priesthood which has been pointed out by the Second Vatican Council. The church has promulgated various documents to this urgent need. One aspect of the ongoing formation is priesthood collegiality to Jesus Christ as high priest, to church where is incardinated, to hierarchy as his institution, to the other priests as his colleagues and to lay people who is also his peer of pastoral service. The intention this writing is to revive priest that the effectiveness and efficacy of pastoral service is collegiality.